JENDRAL ABDUL HARIS NASUTION PAHLAWAN INTELEKTUAL - Diansyah, Arfan; Manurung, Doni Jeremia; Hastatik, Hastatik; Dwitama, Ridho Iqbal; Iqwadan, Rayhan; Yusraini, Rina (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This article aims to find out the profile of an intellectual hero, Abdul Haris Nasution. To obtain the necessary data, researchers used historical research methods consisting of four stages, namely, heuristics, source criticism, data interpretation and historiography. Then the data collection technique is done with literature studies through books, journals and articles available on the internet, as well as documentation by collecting supporting images or photos. The results showed that Abdul Haris Nasution was the initiator of the dual function of ABRI and the foundation of his guerrilla warfare as outlined in the book Gerilya Principles during the Dutch military aggression at that time to break the Dutch attack. The war is known to attack suddenly, then disappear quickly before the enemy has time to counterattack. Apart from being the originator of guerrilla warfare, Abdul Haris Nasution also contributed to the dual function of ABRI by formulating the dual function of ABRI, which was then known as the